2022
DOI: 10.3389/fvets.2022.916461
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Monitoring of Antimicrobial-Resistant Escherichia coli and Enterococcus spp. Isolated From Diseased and Healthy Dogs and Cats in Japan

Abstract: The Japanese Veterinary Antimicrobial Resistance Monitoring System (JVARM) was established for nationwide monitoring of antimicrobial-resistant bacteria isolated from animals. Here, antimicrobial resistance of Escherichia coli and Enterococcus spp. isolates from diseased and healthy dogs and cats was investigated. Isolates were collected from diseased dogs and cats and from healthy dogs and cats in 2018 to 2020. Minimum inhibitory concentrations were determined for 1873 E. coli and 1383 Enterococcus spp. isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…These results agree with those reported in other studies carried out in Europe, with the results from Italy being the most similar to those of the present study [30]. Other authors have also reported the highest AMR to this antibiotic, ranging from 40 to almost 100% in different studies worldwide, regardless of whether they were studies carried out in asymptomatic [47][48][49][50] or symptomatic [43,44,[51][52][53][54] dogs and cats. Moreover, these results have also been found in food-producing animals [17] and humans [51,55], which highlights the global impact of this issue.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those reported in other studies carried out in Europe, with the results from Italy being the most similar to those of the present study [30]. Other authors have also reported the highest AMR to this antibiotic, ranging from 40 to almost 100% in different studies worldwide, regardless of whether they were studies carried out in asymptomatic [47][48][49][50] or symptomatic [43,44,[51][52][53][54] dogs and cats. Moreover, these results have also been found in food-producing animals [17] and humans [51,55], which highlights the global impact of this issue.…”
Section: Discussionsupporting
confidence: 93%
“…In this investigation, it was observed that a major proportion of E. coli isolates exhibited resistance to cefalexin. Consistent with previous reports [18,19], we found high cefalexin resistance rates in E. coli recovered from dogs and cats. Furthermore, significant resistance rates were also noted for ampicillin, tetracycline, and cefazolin in E. coli isolated from different countries, including Korea [15] and the U.S.A. [11].…”
Section: Discussionsupporting
confidence: 93%
“…Fisher's exact test was used to identify differences in the MRSA-positive farm and sample rates between 2018 and the other year and the resistance rates between ST398 and ST5. A probability of p < 0.05 was considered statistically significant [48].…”
Section: Statistical Analysesmentioning
confidence: 99%